Peasant Movement for Land in the Prefecture of Elbasan (Albania) in the Early 20s - 30s of XX Century - Gjevori, Florinka (Mediterranean Journal of Social Sciences, 2012)
Article we present, aims to present an aspect of local history of Elbasan region or neighborhood, in the '20s-30s of thetwentieth century, peasant struggle for land, as one of the main directions of social conflict in this period, not only in the prefecture, butnationwide. This war not only aimed at resolving the land ownership right, but simultaneously improving the economic status ofpeasants, through easing the tax burden. To realize these goals in such a motion also included rural layers of Elbasan Prefecture, whosewar took more the character of an economic war, given the difficult situation that characterize this layer and poor rural schools, especiallythe remote areas and state fiscal policy seriously. Through archival sources, in this article we try to analyze the reasons that promptedsuch a move, the development of its format, the connection with labor movements and their consequences in this region and beyond.